Adoption of tax e-filing: A conceptual paper - Che Azmi, A.A.; Kamarulzaman, Y. (Academic Journals, 2010)
E-government is becoming increasingly more important in today’s world due to its effectiveness and applicability in various areas. Tax e-filing is one of the e-government services that have been adopted by many developed countries today where the public has to discharge their responsibility to the government via online tax filing. Despite the rapid adoption of tax e-filing in many countries, researchers have argued that it is yet to establish an integrated system that is reliable, especially in developing countries like Malaysia due to high perceived risk by the public. Evidence shows that the marketing strategies and organisation commitment throughout the hierarchy is trivial, however, it is lacking in some countries, particularly in Asian countries. This implies that it will be very difficult, if not impossible, to truly embed responsible behaviour within a community if individual perceptions of risk of the e-government service is the issue. The paper aims to study the relationship of perceived risk and its facets within the technology acceptance model (TAM) within the tax e-filing context. This paper proposes a conceptual model to further understand the role of perceived risk in influencing consumer behaviour throughout the adoption process. This paper is then developed into concrete research hypotheses for future studies. The model will serve as a useful guideline for strategies development in promoting e-government services, particularly the tax e-filing service.